Peran Aglomerasi dalam Penyebaran Investasi Asing Langsung (FDI) - Rejeki, Indah Sri; Lubis, Andi Fahmi (UI Scholars Hub, 2019)
For Indonesia and other developing countries where domestic savings are limited, foreign direct investment (FDI) is a main choice in financing industrial manufacturing development. The problem is that the geographical distribution of FDI is not evenly distributed between provinces in Indonesia. This research empirically analyzes the role of agglomeration in the distribution of FDI in Indonesian Manufacturing Industry. Unlike most previous studies, FDI data available by provinces in Indonesia are aggregated into 2-digit ISIC industry from 2010 to 2014. This is intended to enrich the results of previous studies which mostly assume the effect of agglomeration on FDI is the same for all sectors. By using the Generalized Least Square (GLS) regression method, this research has proven the positive influence of agglomeration on the distribution of FDI. The existence of agglomeration which is measured by localization index and manufacturing density index certainly enhances a provincial’s attractiveness to foreign investment. In addition, besides agglomerations, factors affecting the distribution of manufacturing FDI in Indonesia are infrastructure, PDRB per capita, capital intensity, wages, and labor productivity.